Bear and Bird : the adventure and other stories - Jarvis, 1985- (Jarvis, 1985- Bear and Bird., 2024)
Starring best friends Bear and Bird, this delightful collection of stories finds the pair dealing with mix-ups and misunderstandings that result in realizations that strengthen their friendship.